AIR-SEA FLUX OF CO2 IN THE WATERS OF KARIMUNJAWA ISLAND, INDONESIA - Nurul Latifah; Sigit Febrianto; Anindya Wirasatriya; Hadi Endrawati; Muhammad Zainuri; Suryanti Suryanti; Andreas Nur Hidayat (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2020)
The purpose of this study was to determine the distribution of CO2 flux in Karimunjawa in the east monsoon.  The variables in this study were temperature; pH; salinity; DO; CO2 atm was measured using a CO2 meter; chlorophyll-a, phosphate, silicate were measured spectrophotometric method. Total Alkalinity / TA was measured using the titration method with the principle of changing pH; DIC (Dissolved Inorganic Carbon) was measured using CO2sys software. The partial pressure of seawater carbon dioxide calculated using formula: pCO2sea = 6.31T2 + 61,9 Chla2 – 365.85T – 94.41 Chl-a +5715.94, the partial pressure of atmospheric carbon dioxide calculated using formula: pCO2atm = xCO2atm (pb - pH2O).  The calculation of the estimated CO2 flux using the formula: Flux CO2 = Kh x kwa x (∆pCO2)  , if the CO2 flux has a positive value water acts as a CO2 source, and if it is negative, the waters act as a CO2 sink..  CO2 flux in Karimunjawa waters during east monsoon (represented by August 2018) showed that in Karimunjawa waters with normal pH 7.2-7.4 were dominated by bicarbonate ion HCO3-with an average value of  DIC 1847.24 µmol/kg dan TA 1912.51 µmol/kg.  The partial pressure of seawater CO2 is higher than the partial pressure of atmospheric CO2  this indicates that the role of Karimunjawa waters as a source of CO2 where there is release of carbon dioxide into the atmosphere with CO2 flux values ranging from 8.549 – 13.272 mmol m-2 day-1.  The variables that affect the flux of CO2 were the pCO2sea and ΔpCO2 with a very strong and positive correlation. These two variables were influenced by sea water temperature, salinity, chlorophyll-a, phosphate and silicate.